Role of bacterial pathogens in microbial ecological networks in hydroponic plants - Liu, Wenyi; Zhang, Zhihua; Zhang, Bin; Zhu, Yi; Zhu, Chongwen; Chen, Chaoyong; Zhang, Fangxu; Liu, Feng; Ai, Jixiang; Wang, Wei; Kong, Wuyuan; Xiang, Haoming; et al. (Frontiers in Plant Science, 2024)
Plant-associated microbial communities are crucial for plant growth and health. However, assembly mechanisms of microbial communities and microbial interaction patterns remain elusive across vary degrees of pathogen-induced diseases. By using 16S rRNA high-throughput sequencing technology, we investigated the impact of wildfire disease on the microbial composition and interaction network in plant three different compartments. The results showed that pathogen infection significantly affect the phyllosphere and rhizosphere microbial community. We found that the primary sources of microbial communities in healthy and mildly infected plants were from the phyllosphere and hydroponic solution community. Mutual exchanges between phyllosphere and rhizosphere communities were observed, but microbial species migration from the leaf to the root was rarely observed in severely infected plants. Moreover, wildfire disease reduced the diversity and network complexity of plant microbial communities. Interactions among pathogenic bacterial members suggested that Caulobacter and Bosea might be crucial “pathogen antagonists” inhibiting the spread of wildfire disease. Our study provides deep insights into plant pathoecology, which is helpful for the development of novel strategies for phyllosphere disease prediction or prevention.